2016
DOI: 10.1111/mbe.12105
|View full text |Cite
|
Sign up to set email alerts
|

Does (Non‐)Meaningful Sensori‐Motor Engagement Promote Learning With Animated Physical Systems?

Abstract: Previous research indicates that sensorimotor experience with physical systems can have a positive effect on learning. However, it is not clear whether this effect is caused by mere bodily engagement or the intrinsically meaningful information that such interaction affords in performing the learning task. We investigated (N = 74), through the use of a Wii Balance Board, whether different forms of physical engagement that was either meaningfully, non-meaningfully, or minimally related to the learning content wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
2
15
1
Order By: Relevance
“…Significant results of this item ( Paas, 1992 ) indicating less cognitive load for static forms of instruction compared to animations were found in one trial of a related study (Experiment 1 in Wong et al, 2015 ). In contrast, other embodiment studies did not reveal significant effects using variants of this item (e.g., Ruiter et al, 2015 ; Pouw et al, 2016a ). The mental effort item developed by Paas (1992) has been used in various studies to compute the instructional efficiency ( Paas and van Merriënboer, 1993 ) of learning interventions (e.g., Castro-Alonso et al, 2014 ).…”
Section: Cognitive Load Theorycontrasting
confidence: 78%
See 2 more Smart Citations
“…Significant results of this item ( Paas, 1992 ) indicating less cognitive load for static forms of instruction compared to animations were found in one trial of a related study (Experiment 1 in Wong et al, 2015 ). In contrast, other embodiment studies did not reveal significant effects using variants of this item (e.g., Ruiter et al, 2015 ; Pouw et al, 2016a ). The mental effort item developed by Paas (1992) has been used in various studies to compute the instructional efficiency ( Paas and van Merriënboer, 1993 ) of learning interventions (e.g., Castro-Alonso et al, 2014 ).…”
Section: Cognitive Load Theorycontrasting
confidence: 78%
“…Still, even studies that include only very basic forms of bodily involvement and action beyond standard user interfaces are currently presented as being linked to embodiment research (e.g., Agostinho et al, 2015 ; Dubé and McEwen, 2015 ). Though, a large number of studies focusing on embodied learning deal with more sophisticated learning scenarios involving technology such as tangible user interfaces (e.g., Pouw et al, 2016a ; Skulmowski et al, 2016 ) and mixed reality environments (e.g., Johnson-Glenberg et al, 2014 , 2016 ). Therefore, the term embodied learning scenarios currently needs to be interpreted broadly (see Johnson-Glenberg et al, 2014 , for a taxonomy).…”
Section: Embodied Learning Scenarios and Cognitive Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in accordance with previous research showing superior memory for schema-congruent versus incongruent events (e.g., Brod et al, 2017;Brod et al, 2015). The negative effect of gesturing on memory also contradicts previous studies showing that gesturing can improve children's learning in a more educational setting, such as, for example, learning a foreign language (Macedonia & Klimesch, 2014;Macedonia & Knösche, 2011;Toumpaniari et al, 2015), new concepts (e.g., Ping & Goldin-Meadow, 2008;Pouw et al, 2016;Valenzeno et al, 2003), or geography (Mavilidi et al, 2016), and the finding of Feyereisen (2009) that enacting enhances memory for (in)congruent information. It has to be noted that the abovementioned studies all used representational gestures (i.e., gestures that represent visual aspects of concrete features of the learning material).…”
Section: Discussionsupporting
confidence: 88%
“…From an educational perspective, this knowledge about distinctive developmental trajectories of brain structures and accompanying functions is highly relevant as is the study on gesturing as a learning tool. Earlier evidence has already shown that gesturing can improve children's learning of foreign language (Macedonia & Klimesch, ; Macedonia & Knösche, ; Toumpaniari, Loyens, Mavilidi, & Paas, ), new concepts (e.g., Ping & Goldin‐Meadow, ; Pouw, Eielts, Van Gog, Zwaan, & Paas, ; Valenzeno, Alibali, & Klatzky, ) and geography (Mavilidi, Okely, Chandler, & Paas, ). These positive effects of gesturing are interesting and might have important practical implications because gestures are easy to implement in the classroom and are free of cost.…”
Section: The Present Studymentioning
confidence: 99%